Investigation on the ablation behavior of cemented tungsten carbide by a nanosecond UV laser. (November 2021) - Chu, Chenglong; Zhang, Quanli; Zhuo, Hangyu; Zhang, Zhen; Zhu, Yandan; Fu, Yucan
Abstract: The precision machining of hard and ultra-hard materials by the laser beam is a key subject in the field of the modern manufacturing process. To improve the surface quality, the ablation threshold of a single pulse and the influence of the laser parameters on the surface characteristics of cemented tungsten carbide (WC-8Co) are firstly quantified and explored, where the material melting, the evaporation and the phase explosion are involved. The results also show that the scanning speed and the scanning times play important roles on the material removal efficiency. In addition, the crack formation seems to be inevitable under various parameters, where surface cracking in a certain direction to the laser scanning direction caused by the temperature gradient is found. The oxidization behavior is investigated by the XPS, the EDS and the Raman spectrum, which indicates that the main oxidation products are identified to be WO3, CoWO4, Co3 O4 and CoO.